2017
DOI: 10.1007/s12022-017-9500-9
|View full text |Cite
|
Sign up to set email alerts
|

Well-Differentiated Thyroid Cancer Neovasculature Expresses Prostate-Specific Membrane Antigen—a Possible Novel Therapeutic Target

Abstract: Prostate-specific membrane antigen (PSMA), a type II transmembrane glycoprotein receptor, is highly expressed in prostate cancer and in the tumor neovasculature of colon, breast, and adrenocortical tumors. Here, we analyzed PSMA expression in the neovasculature of various thyroid cancer subtypes and assessed whether PSMA expression is correlated with aggressive behavior. From a prospectively maintained database, we evaluated 91 samples from 68 patients, including 37 primary differentiated thyroid cancers (DTCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Moore et al investigated 37 patients and found PSMA significantly overexpressed in the neovasculature of DTC, particularly in RAI-refractory patients and in distant metastases. No PSMA expression was seen on the tumor cells [13]. Recently, in a study including 59 DTC patients, Sollini et al found PSMA positivity in microvessels in 80%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moore et al investigated 37 patients and found PSMA significantly overexpressed in the neovasculature of DTC, particularly in RAI-refractory patients and in distant metastases. No PSMA expression was seen on the tumor cells [13]. Recently, in a study including 59 DTC patients, Sollini et al found PSMA positivity in microvessels in 80%.…”
Section: Discussionmentioning
confidence: 95%
“…PSMA is also expressed in the neovasculature of other tumors including carcinomas of the lung, breast, colorectum, and thyroid [8][9][10][11][12]. Compared to normal thyroid tissue, PSMA is significantly overexpressed in the neovasculature of DTC, especially in the RAI-refractory type [13]. Altogether, PSMA is a potential target for theranostics in RAI-refractory DTC.…”
Section: Introductionmentioning
confidence: 99%
“…In a study examining 91 samples of thyroid cancer, PSMA expression was expressed only in cancer neovasculature and not in the tumour cells, and was not detected in normal thyroid tissue . The subtypes of thyroid cancer where neovasculature expressed the highest levels of PSMA were papillary, radioactive iodine‐refractory and follicular thyroid tumours .…”
Section: Introductionmentioning
confidence: 99%
“…The first evidence of PSMA expression in DTC was provided by Verburg et al [11], who performed 68 Ga-PSMA PET/CT imaging of a patient with 131 I-negative scintigraphy who was bearing metastatic poorly differentiated DTC. More recently, immunohistochemical assessment of PSMA expression revealed it to be highly irregularly expressed by thyroid tumors, but not by normal thyroid tissue [12, 14, 15]. PSMA expression has been reported to be significantly associated with tumor size, vascular invasion in follicular carcinoma [12], and poorly or undifferentiated subtypes [14].…”
Section: Introductionmentioning
confidence: 99%